Patients Satisfaction with Services Obtained from a Health Care Centre in Rural Bangladesh - Mahejabin, Farzana; Khan, Rezaul Farid; Parveen, Shamima (Delta Medical College Journal, 2016)
Background: Patients satisfaction is one of the established yard sticks to measure success of the services being provided in the hospitals. Human satisfaction is a complex concept. A satisfied patient is more likely to develop a deeper and longer lasting relationship with their medical providers, leading to improved compliance, continuity of care, and ultimately better outcomes. Objective: To assess patient satisfaction with services provided in a primary health care centre in rural Bangladesh. Materials and method: This descriptive cross sectional study was carried out among the patients who attended the outpatient department at Upazilla Health Complex, Dhamrai from November 2015 to January 2016. Study subjects were selected by convenient type of non-probability sampling. Semi-structured pre-tested questionnaire was used and face to face interview was conducted. A Total of 328 respondents, age more than 18 years,irrespective of sex, were included in this study. Results: Majority of the patients stated that the general basic facilities, in terms of lighting facilities, signboards, canteen services and toilet facilities at the hospital were adequate. Majority respondents reported that the hospital was clean, ventilation facilities were found adequate, sitting arrangements and drinking water was available in waiting rooms. Most of the patients were satisfied with the behaviour of health personnel and quality of professional services provided by doctors. Regarding overall satisfaction, 44.2% patients were satisfied with health services and only 3.0% patients were dissatisfied. A high statistically significant relation was found between educational level and occupation with satisfaction level of the respondents. Conclusion: The health care delivered at this centre can be improved further by monitoring the delivery ofquality care by ongoing basis and continually making small changes as per need so as to improve the individual processes. Delta Med Col J. Jul 2016 4(2): 77-82